Application of basket geothermal heat exchangers for sustainable greenhouse cultivation. (September 2020) - Barbaresi, A.; Maioli, V.; Bovo, M.; Tinti, F.; Torreggiani, D.; Tassinari, P.
Abstract: The residential building sector is recently experiencing a large reduction of energy demand for conditioning, nevertheless, the use of energy in agro-industrial productions is constantly growing and the research of alternative and more sustainable sources has become necessary. In the greenhouses production, the energy problem is relevant since high demand is required, even for long periods with considerable peak requests and the use of renewable energy sources in such productions can allow a significant reduction of fossil fuel consumptions, greenhouse gas emissions and running costs. In this context, this paper analyses the performance of a low-enthalpy geothermal system, consisting of basket geothermal heat exchangers with a ground source heat pump, specifically studied to provide the base load for winter heating demand of a greenhouse. Due to the large thermal demand requested by the greenhouse, the existent pressurized gas boiler and two existent air source heat pumps, now also converted to work in heating mode, cover the remnant demand. Based on the thermo-hygrometric data, collected during an experimental campaign carried out on a case study farm, the study evaluates the performance of the geothermal system prescribing the optimal thermo-hygrometric conditions requested for the production of three different protected crops. The shallow geothermal field operates mainly during the night-time, allowing the thermal recover of the ground during the daytime. The results provide an assessment of the performances of the hybrid system in terms of primary energy needs, running costs and CO2 with respect to the existent system. Graphical abstract: Image 1 Highlights: BGHE used in hybrid configuration can improve greenhouse cultivation sustainability. The performance of the shallow geothermal field is evaluated and discussed. The numerical results are obtained from experimental data. Hybrid system allows primary energy savings from 20% to 40%. GHG emissions and running costs can be reduced from 10% to 30%.